Multiple Functions of RNA Methylation in T Cells: A Review - Chao, Yinong; Li, Hua-Bing; Zhou, Jing (Frontiers in Immunology, 2021)
RNA modification represents one of the most ubiquitous mechanisms of epigenetic regulation and plays an essential role in modulating cell proliferation, differentiation, fate determination, and other biological activities. At present, over 170 types of RNA modification have been discovered in messenger RNA (mRNA) and noncoding RNA (ncRNA). RNA methylation, as an abundant and widely studied epigenetic modification, is crucial for regulating various physiological or pathological states, especially immune responses. Considering the biological significance of T cells as a defense against viral infection and tumor challenge, in this review, we will summarize recent findings of how RNA methylation regulates T cell homeostasis and function, discuss the open questions in this rapidly expanding field of RNA modification, and provide the theoretical basis and potential therapeutic strategies involving targeting of RNA methylation to orchestrate beneficial T cell immune responses.